Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given that $P, Q, R$ is a function of $x, y, z$, we have $$ P {\partial z \over \partial x} + Q{\partial z \over \partial y} = R \hspace{2 cm} (1)$$ The book says that $ u = \phi(v) $ is the solution of $(1)$ if $\phi(u, v) = 0$ is the solution of $$ {dx \over P} = {dy \over Q} ={dz \over R} \hspace{2 cm} (2)$$ where $\phi$ is an arbitrary function. I don't understand why my book is giving the solution as $ \phi(u, v) = 0$ sometimes while $u = \phi(v)$ at other times.

Examples: Let $p = {\partial z \over \partial x} $ and $q = {\partial z \over \partial y} $

Problem 1:- ${y^2zp \over x} + xzq = y^2$, Solution: $f(x^2-z^2, x^3-y^3) = 0$
Problem 2:- $(x+2z)p + (4zx-y)q = 2x^2+y$, Solution: $x^2-y-z =f(xy-z^2)$

When do we have a solution of type $\phi(u, v) = 0$ and when is it of type $ u = \phi(v) $?

share|improve this question
add comment

1 Answer 1

up vote 2 down vote accepted

It's worth recalling that the vector $(-z_x,-z_y,1)$ is a normal vector to the surface $z=z(x,y)$. Our equation (1) says precisely that the normal vector must be orthogonal to the given vector field $(P,Q,R)$. This makes it natural to look for solutions in the implicit form $F(x,y,z)=0$, because the orthogonality relation becomes $\nabla F\perp (P,Q,R)$. There is a lot of freedom here: the set of possible gradients $\nabla F$ is two-dimensional at every point. We can hope to cover all solutions by choosing two "independent" ones, $u(x,y,z)=0$ and $v(x,y,z)=0$, and then letting $F=\phi(u,v)$ where $\phi$ can be any smooth function.

One practical way to find $u$ and $v$ is to look at the fields such as $(-Q,P,0)$, $(-R,0,P)$ and $(0,-R,Q)$ (which are orthogonal to $(P,Q,R)$ by design) and try to make them conservative by introducing a scalar factor (aka integrating factor). Let's try this in problem 1. We have the field $(y^2z,x^2z,xy^2)$ (no harm in multiplying by $z$ throughout). Noticing the common factor of $y^2$, we go for $(-R,0,P)=y^2(-x,0,z)$ where $(-x,0,z)=\nabla (-x^2+z^2)/2$. This gives $u$. Similarly, there is a common factor of $z$ in the first two components, and without it we get $(-x^2,y^2,0)$, which gives $v$.

But in problem 2 this won't work because we can't get rid of any of three variables by isolating it to a scalar factor. Instead we can try additive cancellation. For example, adding $Q+R$ cancels $y$, and the result is nothing but $2xP$. So, $(-2x,1,1)\perp (P,Q,R)$ which gives $u=-x^2+y+z$ as one of solutions. Similarly, $yP+xQ$ gets rid of some terms and luckily for us, $yP+xQ=2zy+4zx^2=2zR$. So, $(y,x,-2z)\perp (P,Q,R)$, and we get $v=xy-z^2$. Just as in problem 1, the equation $\phi(-x^2+y+z,xy-z^2)=0$ represents an (implicit) solution for any smooth function $\phi$.

Conclusion: Problem 2 should have solution of the form $\phi(-x^2+y+z,xy-z^2)=0$, just as problem 1. Of course, this includes $\phi(u,v)=u+f(v)$ as a special case. It's possible that in your textbook only this special case was needed for some reason.

share|improve this answer
    
I should add that this is not necessarily how such equations should be solved: I was trying to produce solutions equivalent to your textbook's. A better explanation can be found here. –  user31373 Aug 12 '12 at 22:16
    
thank you very much for response ... i'm going through it. –  hasExams Aug 12 '12 at 23:08
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.